Langage et construction de règles en jeux collectifs - Florence Darnis; Lucile Lafont (Recherches en Éducation)
In a socio-constructivist didactic physical education teaching model, 6 years old pupils have to play at a collective ball game. At the same time, they have to tell each other action rules to be better players. Furthermore, at school, they have to write in a cooperative learning setting attackers action rules and defenders action rules. The results show that they made progress in tactical abilities to make better choices. The language is used to a better action rules understanding in a socio-constructivist physical education didactic model. This research is the result of two years of collaborative work between an academic researcher and a school teacher in a participative research. The descriptive results highlight a teaching game for understanding way to learn language and at the same time it shows language use to better play collective ball games.